2022
DOI: 10.22202/mamangan.v11i2.5854
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Analysis of Coffee Shop Visitors Using Twitter Data

Abstract: The concept of the present and the sense of comfort offered by the coffee shop bring in various visitors in terms of age, children, teenagers, adults, and even the elderly. Visitors in terms of work, both from junior high school, high school/vocational school students, university students, private employees, civil servants, and from various other types of work are happy to visit. The purpose of this study was to conduct a social network analysis of coffee shop visitors in Indonesia. The postmodern concept of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…This research is in line or relevant to the research of Arhas et al, (2021) saying that "setting implementation or planning standards is very important to be set as a benchmark and measure of assessment of the results of the activities carried out". Based on observations, researchers found that employees in the secretariat of the Sinjai Regency DPRD increased their work discipline if implementation standards were set because they had benchmarks in carrying out all activities or activities in the office.…”
Section: Establishment Of Implementation or Planning Standardsmentioning
confidence: 62%
“…This research is in line or relevant to the research of Arhas et al, (2021) saying that "setting implementation or planning standards is very important to be set as a benchmark and measure of assessment of the results of the activities carried out". Based on observations, researchers found that employees in the secretariat of the Sinjai Regency DPRD increased their work discipline if implementation standards were set because they had benchmarks in carrying out all activities or activities in the office.…”
Section: Establishment Of Implementation or Planning Standardsmentioning
confidence: 62%
“…Direct evidence in measuring the quality of student administration services at SMK Negeri 8 Makassar can be measured through indicators of room tidiness, office cleanliness, and completeness of facilities and infrastructure. In line with the theory put forward by (Arhas et al, 2021) that the era of service facilities is very important and one that is very influential on improving the quality of public services because with the existence of adequate service facilities Volume 2, Number 1, January-April 2023, Page 31-40 can make services to the community can provide more comfort and satisfaction in the serviceroom.…”
Section: Direct Evidence (Tangible)mentioning
confidence: 77%
“…The data collection technique used in this study is in the form of documentation techniques with ethnographic studies, namely data collection techniques that examine the interactions of various interdisciplinary groups in cyberspace (Arhas et al, 2022;. The documentation technique is carried out by collecting data in the form of poster photos regarding the prevention of Covid-19.…”
Section: Methodsmentioning
confidence: 99%